Rhenium (I) Complexes as Probes for Prokaryotic and Fungal Cells by Fluorescence Microscopy: Do Ligands Matter? - Otero, Carolina; Carreño, Alexander; Polanco, Rubén; Llancalahuen, Felipe M.; Arratia-Pérez, Ramiro; Gacitúa, Manuel; Fuentes, Juan A. (Frontiers in Chemistry, 2019)
Abstract Re(I) complexes have exposed highly suitable properties for cellular imaging (especially for fluorescent microscopy) such as low cytotoxicity, good cellular uptake, and differential staining. These features can be modulated or tuned by modifying the ligands surrounding the metal core. However, most of Re(I)-based complexes have been tested for non-walled cells, such as epithelial cells. In this context, it has been proposed that Re(I) complexes are inefficient to stain walled cells (i.e. cells protected by a rigid cell wall, such as bacteria and fungi), presumably due to this physical barrier hampering cellular uptake. More recently, it has been published a series of studies showing that a suitable combination of ligands is useful to obtaining Re(I)-based complexes able to stain walled cells. This review summarizes main characteristics of different fluorophores used in bioimage, remarking the advantages of d6-based complexes, and focusing on Re(I) complexes. In addition, we explored different structural features of these complexes that allow obtaining fluorophores especially designed for walled cells (bacteria and fungi), with especial emphasis in the ligand choice. Since many pathogens correspond to bacteria and fungi (yeasts and molds), and considering that these organisms have been increasingly used in several biotechnological applications, development of new tools for their study, such as the design of new fluorophores, is fundamental and attractive.